Inkarnasi dan Asensi: Relasi yang Terlupakan dari Dua Doktrin - Joas Adiprasetya (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2022)
This study focuses on the relationship between the doctrines of the Incarnation and the Ascension of Jesus Christ, which often does not receive adequate attention in contemporary theology. The problem of separating the two doctrines is solved by re-examining the doctrine of the hypostatic union of Christ in the Lutheran and Calvinist traditions. Analytical and comparative approaches to the two traditions are undertaken to clearly show the tensions that arise and the possibility of imaginatively and faithfully linking the Incarnation and the Ascension. The study of these two models is furthered by comparing the two contemporary responses of the two traditions, one by Thomas Torrance and another by Niels Gregersen, that results in two ways of understanding Ascension, both as a reversal and as an extension.